Prediction of Sentinel Node Status and Clinical Outcome in a Melanoma Centre - Vera Teixeira; Ricardo Vieira; Inês Coutinho; Rita Cabral; David Serra; Maria José Julião; Maria Manuel Brites; Anabela Albuquerque; João Pedroso de Lima; Américo Figueiredo (Journal of Skin Cancer)
Background. Sentinel lymph node biopsy (SLNB) is a standard procedure for patients with localized cutaneous melanoma. The National Comprehensive Cancer Network (NCCN) Melanoma Panel has reinforced the status of the sentinel lymph node (SLN) as an important prognostic factor for melanoma survival. We sought to identify predictive factors associated with a positive SLNB and overall survival in our population. Methods. We performed a retrospective chart review of 221 patients who have done a successful SLNB for melanoma between 2004 and 2010 at our department. Univariate and multivariate analyses were done. Results. The SLNB was positive in 48 patients (21.7%). Univariate analysis showed that male gender, increasing Breslow thickness, tumor type, and absence of tumor-infiltrating lymphocytes were significantly associated with a positive SLNB. Multivariate analysis confirmed that Breslow thickness and the absence of tumor-infiltrating lymphocytes are independently predictive of SLN metastasis. The 5-year survival rates were 53.1% for SLN positive patients and 88.2% for SLN negative patients. Breslow thickness and the SLN status independently predict overall survival. Conclusions. The risk factors for a positive SLNB are consistent with those found in the previous literature. In addition, the SLN status is a major determinant of survival, which highlights its importance in melanoma management.